Population based need assessment of palliative care in rural Nepal (Journal of Patan Academy of Health Sciences, 2017)
Introductions: Developing palliative care in rural Nepal is essential to integrate the service into the national health system. This study was done with the aim of assessing the need of patients requiring palliative care in rural Nepal.Methods: This was a cross-sectional population based study in Thaha Municipality using a 30-cluster sampling method and employing the Supportive and Palliative Care Indicators Tool (SPICT) to identify patients with palliative care need. Assessment of symptom burden was done for patients identified to have palliative care need.Results: Out of 330 households with a population of 2168, we found 139 (6.4%) suffering from chronic non-communicable diseases and 66 (3.04%) met the SPICT criteria for palliative care need and 60% were elderly above the age of 60. The disease of respiratory system followed by frailty and dementia were common condition requiring palliative care.Conclusions: This study showed a high level of need for palliative care in a rural population in Nepal. This needs to be considered in further planning of health services in the country.